Radiocarbon Dating of the Transition from the Early to the Middle Bronze Age in Northeastern Syria. Issue 4 (10th June 2019) - Koliński, Rafał; Goslar, Tomasz
ABSTRACT: The paper presents radiocarbon ( 14 C) dates of samples collected from the Bronze Age cultural strata (VI–II) excavated within Sector P, Tell Arbid, Khabur Triangle, northern Mesopotamia. These strata contain objects (remains of a caravanserai, pits, graves, pottery kilns, and multi-phase houses) representing the periods of Early Jezirah 4-5, and Old Jezirah I-II. 14 C dating of these strata was especially important because of a clearly visible period of abandonment of the area at the onset of 2nd millennium BC, recorded on all Khabur Triangle sites studied so far, and because of the questionable reliability of the chronology derived from scarce historical sources. Of the 29 samples of cereal grains, 9 appeared to contain residual material, while Bayesian-analyzed 14 C ages of the remaining 20 allowed us to say that, at the turn of the 3rd millennium BC, Tell Arbid was abandoned later than other sites in the area, and that it was occupied over a distinctly longer period during the early 2nd millennium.